2017
DOI: 10.1159/000481753
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone Attenuates the Proinflammatory Response in Amyloid-β-Treated Microglia by Inhibiting NLRP3 Inflammasome-Mediated IL-1β Secretion

Abstract: Background/Aims: Microglial activation is an important pathological feature in the brains of patients with Alzheimer's disease (AD), and amyloid-β (Aβ) peptides play a crucial role in microglial activation. In addition, edaravone (EDA) was recently shown to suppress oxidative stress and proinflammatory cytokine production in APPswePS1dE9 (APP/PS1) mice. However, the mechanism by which EDA inhibits the Aβ-induced proinflammatory response in microglia is poorly understood. Methods: The mitochondrial membrane pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 33 publications
1
34
1
Order By: Relevance
“…However, several reports have demonstrated that administration of edaravone inhibited systemic or local inflammation associated with oxidative stress in various tissues. It suggested that edaravone indirectly suppresses inflammation by protecting against tissue damage via scavenging of free radicals (Zhang et al, 2005;Yoshida et al, 2006;Fujiwara et al, 2016;Wang et al, 2017). In this study, edaravone showed FIGURE 8 | The muscle ischemic-injured score showed that pretreatment with the edaravone significantly inhibited muscle injury at 7 days after ischemia in both control (Con) and obese (Ob) mice ( * compared to mice without administration of edaravone, p < 0.05).…”
Section: Discussionmentioning
confidence: 49%
“…However, several reports have demonstrated that administration of edaravone inhibited systemic or local inflammation associated with oxidative stress in various tissues. It suggested that edaravone indirectly suppresses inflammation by protecting against tissue damage via scavenging of free radicals (Zhang et al, 2005;Yoshida et al, 2006;Fujiwara et al, 2016;Wang et al, 2017). In this study, edaravone showed FIGURE 8 | The muscle ischemic-injured score showed that pretreatment with the edaravone significantly inhibited muscle injury at 7 days after ischemia in both control (Con) and obese (Ob) mice ( * compared to mice without administration of edaravone, p < 0.05).…”
Section: Discussionmentioning
confidence: 49%
“…In the last few years, numerous studies have been conducted in the exploration of therapeutic pathways against neurodegenerative diseases through the inhibition of the NLRP3 inflammasome. For the studies of Alzheimer’s disease, it was recently reported that edaravone, a recently shown oxidative stress suppressor, functioned in attenuating the β-amyloid-induced proinflammatory response in microglia ( Wang et al, 2017 ). This effect was through the reduction of mitochondria-derived reactive oxygen species (ROS) production and increased manganese superoxide dismutase (SOD-2) activity, thus leading to the inhibition of the NLRP3 inflammasome-mediated proinflammatory secretion ( Wang et al, 2017 ).…”
Section: Nlrp3 Inflammasome In Cns Disordersmentioning
confidence: 99%
“…For the studies of Alzheimer’s disease, it was recently reported that edaravone, a recently shown oxidative stress suppressor, functioned in attenuating the β-amyloid-induced proinflammatory response in microglia ( Wang et al, 2017 ). This effect was through the reduction of mitochondria-derived reactive oxygen species (ROS) production and increased manganese superoxide dismutase (SOD-2) activity, thus leading to the inhibition of the NLRP3 inflammasome-mediated proinflammatory secretion ( Wang et al, 2017 ). Furthermore, depeptidyl vinyl sulfone, a chemical agent, was demonstrated to suppress the high-mobility group box protein-1 (HMGB1)/NLRP3 inflammasome-related inflammation in β-amyloid-stimulated microglia, which was involved in the decrease of the two inflammation-related microRNA including microRNA-155 and microRNA-146a ( Falcao et al, 2017 ).…”
Section: Nlrp3 Inflammasome In Cns Disordersmentioning
confidence: 99%
“…The activation of NLRP3 inflammasome triggers the transformation of procaspase-1 to caspase-1 and catalyzes the exudation of mature IL-1β and IL-18 from pro-IL-1β and pro-IL-18, causing an inflammatory response [45,46]. Previous studies showed that ROS, especially from mitochondria, activated the NLRP3 inflammasome [47,48]. The current findings proposed that the expression of ROS, NLRP3, caspase-1, and IL-1β in the LPS group was increased as compared to that in the control groups; however, after the administration of DHLA, the level of NLRP3, caspase-1, and IL-1β decreased markedly.…”
Section: Discussionmentioning
confidence: 99%